Evaluation of resources in the study of industrial and culinary properties for the varietal characterization of rice (Oryza sativa L.) = Evaluación de recursos para el estudio de las propiedades industriales y culinarias para la caracterización varietal de arroz (Oryza sativa L.) - Farco, Andrea P.; Bouchard, José D.; Díaz, Sergio F.; Kruger, Raúl; Maiocchi, Marcos G. (Facultad de Ciencias Exactas, Químicas y Naturales, Universidad Nacional de Misiones, 2022)
Different physicochemical tests have been used over time in the Oryza sativa species for the study of industrial and culinary properties. In this study, nine attributes were compared: amylose content, total whiteness, thousand grain weight, grain length and width, gelatinization time, apparent water absorption, expansion ratio, and gelatinization temperature. However, there is no single attribute that allows defining the concept of “culinary quality” in rice, since it depends on its behavior after cooking. The two varieties of long fine polished rice used for this study were: IRGA 424 (Rio Grandense Rice Institute) and Tranquilo FL INTA (National Institute of Agricultural Technology) and a mixture of both. In this work, the characterization of industrial and culinary properties of the rice varieties mentioned above was achieved by evaluating five attributes using simple and low-cost physical-chemical techniques in two of the rice varieties most in demand by producers in the province of Corrientes. This finding would allow the study of rice varieties to be approached by optimizing: equipment, reagents and time in future trials.